The Effect of the Team Members Teaching Design vs. Regular Lectures method on the Self-efficacy of the Multiple sclerosis Patients in Iran. Randomised Controlled Trial - Dehghani, Ali; Fakhravari, Fariba; Hojat, Mohsen (Investigación y Educación en Enfermería, 2024)
Objective. This study was conducted with the aim of the effect of team members teaching design (TMTD) vs. regular Lectures method on the self-efficacy of the multiple sclerosis patients. Methods. This research is a randomized controlled trial study. In this study, 48 multiple sclerosis persons of members of Jahrom MS Society participated. The persons were selected by simple random sampling and then divided into three groups of: TMTD (n=16), regular lecture method (n=16), and control (n=16), by random allocation method. In the intervention groups, six training sessions were held twice a week; control group did not receive education. Data was collected by the MS self-efficacy questionnaire of Rigby et al. in the before, immediately and one month after the intervention. Results. Patients in three intervention and control groups were similar in terms of demographic variables. The results of the repeated measurement test before, immediately and one month after the intervention showed that the mean of the all dimensions of self-efficacy in two intervention groups had increased significantly (p<0.05). While these changes were not significant in the control group (p ≥ 0.05). Also, there was a significant difference in the mean of the all dimensions of self-efficacy between the intervention groups of TMTD and regular lectures. Conclusion. Based on the findings, TMTD compared to regular lectures method had a more significant effect on improving the self-efficacy of multiple sclerosis patients. Therefore, it is recommended that nursing use this educational approach to increase patients’ self-efficacy.